Pelatihan Penyusunan Soal Berbasis High Order Thinking Skill Untuk Guru Biologi di Kabupaten Garut - Rifaatul Muthmainah; Lida Amalia; Leni Sri Mulyani; Asep Rohayat; Hudiana Hernawan (Jurnal Pekemas, 2020)
This community service activity aims to provide skills for biology teachers on making high order thinking skills questions. Through the habituation of the use of HOTS questions, it is expected that students are accustomed and trained to use high-level thinking skills in daily learning. So later students not only memorize the concept of biology, but also have higher thinking skills. The service activity consists of two stages, the first stage is lecture delivery and the second phase is practices on making HOTS questions. The activity was attended by biology teachers who joined MGMP Biology in the scope of madrasah aliyah in garut district. The training material is making of HOTS questions. The results show that community service is well underway. Based on the overall poll results, teachers responded positively to this training. Teachers seem very enthusiastic on listening explanations and practicing. Teachers revealed through this training, they get more practical and clear description on making HOTS questions. Through this training, the college carries out its role to contribute on improving the competence of teachers, especially in the creation of HOTS-based questions. The obstacles that arise are the relatively short allocation of time, considering the skills of making hots questions need to be trained regularly